2005
DOI: 10.1558/sll.2005.12.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Aural and automatic forensic speaker recognition in mismatched conditions

Abstract: In this article, we compare aural and automatic speaker recognition in the context of forensic analyses, using a Bayesian framework for the interpretation of evidence.We use perceptual tests performed by non-experts and compare their performance with that of an automatic speaker recognition system. These experiments are performed with 90 phonetically untrained subjects. Several forensic cases were simulated, using the Polyphone IPSC-02 database, varying in linguistic content and technical conditions of recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Finally, we should mention that our preliminary results confirm exactly what was presented in literature on other databases especially in [10].…”
Section: B Preliminary Resultssupporting
confidence: 91%
“…Finally, we should mention that our preliminary results confirm exactly what was presented in literature on other databases especially in [10].…”
Section: B Preliminary Resultssupporting
confidence: 91%
“…However, Leemann, Kolly, and Dellwo () showed that variations in suprasegmental temporal features are stable across changes in speaking style (spontaneous vs. read). Listeners may therefore be able to rely on stable, high‐level features of speech, such as mannerisms, speaking rate, and pauses when making matching decisions (Alexander, Dessimoz, Botti, & Drygajlo, ).…”
Section: Voice Discrimination Performancementioning
confidence: 99%
“…Fig. 2 provides an example Tippett plot [9,10,21,[45][46][47][48][49][50][51][52] illustrating the improvements due to calibration for /a/ comparison set a. After calibration, the likelihood ratios from /i/ were more accurate than those from /a/, which were in turn more accurate than those from /e/ (compare C llr cal values in Table 1).…”
Section: Resultsmentioning
confidence: 99%